2020
DOI: 10.3389/fimmu.2020.569671
|View full text |Cite
|
Sign up to set email alerts
|

Systems Immunology Analysis Reveals an Immunomodulatory Effect of Snail-p53 Binding on Neutrophil- and T Cell-Mediated Immunity in KRAS Mutant Non-Small Cell Lung Cancer

Abstract: Immunomodulation and chronic inflammation are important mechanisms utilized by cancer cells to evade the immune defense and promote tumor progression. Therefore, various efforts were focused on the development of approaches to reprogram the immune response to increase the immune detection of cancer cells and enhance patient response to various types of therapy. A number of regulatory proteins were investigated and proposed as potential targets for immunomodulatory therapeutic approaches including p53 and Snail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…One ng of RNA of each sample was analyzed using targeted whole RNA-seq with AmpliSeq whole transcriptome on S5 system (Thermo Fisher Scientific), and RNA-seq data were analyzed using the Ion Torrent Software Suite version 5.4. Alignment was carried out using the Torrent Mapping Alignment Program (TMAP), as described in ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…One ng of RNA of each sample was analyzed using targeted whole RNA-seq with AmpliSeq whole transcriptome on S5 system (Thermo Fisher Scientific), and RNA-seq data were analyzed using the Ion Torrent Software Suite version 5.4. Alignment was carried out using the Torrent Mapping Alignment Program (TMAP), as described in ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…The data obtained using lung mesothelioma also showed that blocking the Snail-p53 association with a small molecule, GN25, led to p53 activation ( Cho et al, 2015 ). Also, inhibition of the Snail-p53 axis by GN25 in A549 cells changed the expression profile of genes associated with immunoregulation, increased the expression of IL8, CXCL2, and CD81 ( Hammoudeh et al, 2020 ). Inhibition of p53 through the interaction with Snail occurs in tumors that contain K-Ras mutations.…”
Section: P53-mediated Effects On Emt At the Protein Stability Levelmentioning
confidence: 99%
“…Chemotherapy resistance is a major barrier for breast cancer treatment, and strategies to circumvent resistance are required [58]. Tumors evade the immune system by inducing in ammation [59]. In the early stages of tumor development, the immune response exerts anti-tumor activity, whereas, in the advanced stages, the tumor establishes mechanisms to evade the immune response, thus eliciting a chronic in ammation process that shows a pro-tumor effect [60].…”
Section: Discussionmentioning
confidence: 99%